A mixed method study evaluating the integration of pregnancy weight gain charts into antenatal care. Issue 3 (13th December 2018) - de Jersey, Susan; Guthrie, Taylor; Tyler, Jeanette; Ling, Wan Yin; Powlesland, Hilary; Byrne, Clare; New, Karen
Abstract: Monitoring pregnancy weight can reduce excess gestational weight gain (GWG), and is recommended in clinical practice guidelines as part of routine care. This study aimed to evaluate the implementation of routine weight monitoring using a pregnancy weight gain chart (PWGC), and assess health care professionals (HCPs) and pregnant women's attitudes and practices around its use. A semiquantitative survey was conducted with a consecutive sample of antenatal women at 16 and 36 weeks gestation. Women were weighed, and a PWGC audit done at 36 weeks gestation to assess adherence to chart use and GWG. A cross‐sectional survey of antenatal HCPs at the Australian facility assessed staff attitudes and practices relating to weight monitoring and PWGC use. Of the 291 women surveyed, 68% reported being given a PWGC. Of the audited PWGCs ( n = 258), 54% had less than three weights recorded, 36% had errors, and 3% were unused. All HCPs surveyed ( n = 42) were aware of the PWGC, 63% reported using it to track GWG regularly and 26% believed it to be only the woman's responsibility (i.e., not the midwife's role) to complete it. Seventy‐six percent reported they needed more training in counselling pregnant women, and insufficient time was a main barrier to weighing and conversing with women. It is feasible to implement a PWGC into routine antenatal care. Clarity over women's and HCPs responsibility for monitoring GWG and completion of the PWGC is needed. Training on correct PWGC use and counselling and workforce engagement are required to overcome barriers and support healthy GWG.